Main indications for the use of Cone Beam computadorized tomography in Endodontics (Research, Society and Development, 2025)
Introduction: One of the basic principles of endodontics is the disinfection of root canals, for which proper instrumentation and clear visualization of the preparation are essential. Radiography is indispensable in this process; however, it has limitations due to its two-dimensional visualization of a three-dimensional object. Objective: The aim of this literature review is to examine the main applications of cone beam computed tomography (CBCT) in Endodontics and to provide an overview that enables the dental surgeon to assess its necessity in diagnosis and endodontic treatment planning. Materials and Methods: The research was conducted through electronic searches in the Scielo, Revista ABRO, PubMed, and Google Scholar databases. A total of 62 sources were selected based on the following criteria: publications between 1988 and 2024, full-text articles, and books that, in their content, address topics related to the use of computed tomography in Endodontics. Conclusion: The development of cone beam computed tomography has gained increasing importance in dentistry and endodontics, especially in cases where conventional radiographs do not provide adequate image quality or are insufficient, thereby compromising the clinician’s confidence in decision-making and intervention.